IMPROVING STUDENTS’ SPEAKING SKILL THROUGH DEBATE TECHNIQUE AT SMK SWASTA DHARMA BAKTI MEDAN - Nainggolan, Mesda Pitrina (Kairos English Language Teaching Journal, 2017)
Speaking is important to be learnt because speaking is the way to communicate with other people in order to deliver opinion and express idea. That means there must be at least two peopleÂ in speaking, otherwise it is not called speaking. Speaking is the primary aspect of learning aÂ language because the final goal of language learning is communication. This study is ClassroomÂ Action Research in which the writer employs debate technique in teaching speaking. TheÂ teaching process was carried out in two cycles. The data consist of observation sheet and test.Â The data from the observation that have been taken from every cycle are analyzed descriptively,Â while the data from test are analyzed quantitatively. The result of this study shows that usingÂ debate technique can improve studentsâ€™ speaking skill. This is proven by studentsâ€™ test scoreÂ that improved in each test. In the pre-test, the studentsâ€™ average score is 66.2. While in theÂ formative test cycle I, the studentsâ€™ average score is 67.6, and in the post-test cycle II, theÂ studentsâ€™ average score is 76.3. That means the debate technique can improve the studentsâ€™Â speaking skill significantly.